A REVIEW OF TREATMENT STRATEGIES OF SUPRACONDYLAR FRACTURE OF HUMERUS IN CHILDREN - Aqeel Ahmed Memon; Imtiaz Hashmi; Sohial Rafi; Anisuddin Bhatti; Idress Shah; Asad Aziz (ziauddin University, 2024)
Pediatric supracondylar fracture of distal humerus frequently occurs within 10 years of age with peak at 6-7 years. There is higher incidence of complications such as neurovascular compromise and late cubitusvarus deformity if left untreated at initial stages. This  often  occur  because  of   important  neurovascular  structures  are crossing the  elbow  region  which  hold different  anatomic  characteristics  as  well. This article is based on appraisal of  the  classification,  clinical  evaluation,   and  with  particular  emphasis  on  the management  of each  type  especially  short  term  complications  which  may  occur  with  fracture  displacement.